Hyaline membrane disease: a study of lung function and treatment - Harrison, V C (Department of Paediatrics and Child Health, 2020)
At present, both the aetiology of hyaline membrane disease and a means of preventing it remain unknown. Recent studies indicate that a significant number of infants die of respiratory failure but there is no general agreement concerning the changes of pulmonary function which lead to this stage. Two approaches have been used in the treatment of respiratory decompensation. First it has been proposed that blood gas and acid base abnormalities which result from respiratory failure can be prevented by oxygen and intravenous alkali and secondly an attempt has been made to correct abnormal lung function itself by means of artificial ventilation. These methods are directed at different aspects of the problem and their efficacy is as yet not established. The application of artificial ventilation in particular must depend on the nature of any ventilation, diffusion or perfusion defect.